Community-Based Tourism optimization through institutional entrepreneurship in Sidomulyo Tourism Village - Peni Arianita Wardani; Uystka Hikmatul Kamiliyah NH; Muhamad Farhan (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aimed to analyze the institutional entrepreneurship strategies to optimize community-based tourism practices in Sidomulyo Tourism Village.Method — This qualitative descriptive research focuses on the Tourism Awareness Group as the management institution of Sidomulyo Tourism Village. The data collection techniques are observation in Sidomulyo Tourism Village, in-depth interviews with the managers of the Tourism Awareness Group, and documentation. All discovered data is analyzed using Discursive Institutionalism.Result — We distinguished institutional entrepreneurship strategies into two dimensions: ideas and discourses. These strategic ideas include: managing the tourism village independently, re-justify Tourism Awareness Group goals following CBT aspects, re-arrange the formation and function within the Tourism Awareness Group component, involving the community in every step of the tourism village development, and communities get a fair reward for their participation, promoting community investment, creating product innovations, collaborating with universities and other tourism institutions, and also establish an environmental conservation and cultural preservation program with the community. Then, these ideas must be carried out in coordinative and communicative discourse. The Tourism Awareness Group actors who know communication skills and networks in the tourism sector are needed to convey these ideas.Contribution — This research contributes to discuss institutional entrepreneurship in tourism which still rarely to be studied.